ANALISIS PERBEDAAN ABNORMAL RETURN, VOLUME DAN HARGA PERDAGANGAN SAHAM SEBELUM DAN SESUDAH PENGUMUMAN INDONESIA SUSTAINABILITY REPORTING AWARD (ISRA) - Pebrina Swissia; Feby Eka Putri Darmawan (Jurnal Akuntansi dan Keuangan, 2019)
The objective of this research was to prove empirically the differences between the abnormal return, the trading volume, and the trading price before and after the Indonesia Sustainability Reporting Award (ISRA) announcement. There are 3 independent variables of this research i.e., the abnormal return, the trading volume and the trading price. The population of this research was companies participated in the ISRA award in the period of 2011-2016. The sampling technique used in this research was the purposive sampling. The number of samples of this research was 112 companies obtained during 2011-2016. The data analysis technique used in this research was the wilcoxon signed-rank test. The result of this research was that the trading volume had a significant difference before and after the Indonesia Sustainability Reporting Award (ISRA) announcement; while, the abnormal return and the trade price had an insignificant difference before and after Indonesia Sustainability Reporting Award (ISRA) announcement.